Communication Science Students’ Perception of Somethinc’s Product Discount Promotion Strategy on TikTok - Difa Anugrah Indah Cahyani; Yuliana Astutik; Rio Kurniawan (Literasi Nusantara, 2026)
This study aims to analyze the perceptions of Communication Science students at Universitas Trunojoyo Madura toward Somethinc product discount promotions on TikTok, identify the factors influencing those perceptions, and examine their impact on students’ interest in the products. This research employed a qualitative descriptive approach within a constructivist paradigm. Data were collected through observation, in-depth interviews, and documentation involving five Communication Science students who actively use TikTok and have encountered Somethinc discount promotions on the platform. The findings indicate that students generally have positive perceptions of Somethinc’s discount promotions on TikTok. The promotions are considered attractive, informative, easy to understand, and effective in capturing attention through creative visual content and clear messages. Students’ perceptions are influenced by personal experience, product needs, promotional characteristics, and the intensity of TikTok usage. Furthermore, the promotions increase students’ interest in Somethinc products by encouraging them to seek product information and consider purchasing decisions. The study concludes that discount promotions on TikTok are an effective digital marketing communication strategy for attracting consumer attention and increasing purchase interest among university students.